Microbial Stability of Certain Cured Fishery Products - T., Jawahar Abraham; D., Sukumar; S.A., Shanmugam; P., Jeyachandran (Fishery Technology, 2025)
The microbial stability of cured fishery products processed by improved curing and packaging methods was studied. Improved drying methods resulted in lower microbial counts than trade samples. Slight to strong brown discolouration was noticed during storage in dried anchovy, Stolephorus indicus. The yellow discolouration of dried salted seer appeared to be checked by lil IA treatment. Bl [A treatment in combination with a dip in 3 percent calcium propionate solution was effective in controlling fungal growth and yellow discolouration. Cooking and hot smoking of tuna, Euthynnus affinis, yielded a stable product with lom̌oisture content, while the cold blanched, hot smoked fish spoiled rapidly. ln pickled prawn, Parapenaeopsis stylifera, with condiments and pll level around 4.75, the microbial count was greatly reduced. ln lactic fermented prawn pickle, there was a steep rise in staphylococci count initially which then decreased with the reduction in pH level.